2013
DOI: 10.5398/medpet.2013.36.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Species Authentication of Dog, Cat, and Tiger Using Cytochrome β Gene

Abstract: Adulteration of animal food products for economic reason has happened during the last decades. Species identification method development was needed to prevent falsification information. The objective of this research was to study species authentication (dog, cat, and tiger) to ensure animal origin in products using cyt β gene specific marker. DNA extraction and fragment amplification were conducted using phenol-chloroform and multiplex PCR (Polymerase Chain Reaction) method, respectively. This research showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Previous studies successfully identified various species in the meats with and without temperature treatments by using multiplex PCR mitochondrial DNA cytochrome b gene (Matsunaga et al, 1999;Shin et al, 2006;Ni'mah et al, 2016;Hertanto et al, 2017). Irine et al (2013) also used cytochrome b gene to identify species of tiger, cat, and dog. In addition to cytochrome b gene, another unique region contained in animal mitochondrial genome is 12S rRNA gene.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies successfully identified various species in the meats with and without temperature treatments by using multiplex PCR mitochondrial DNA cytochrome b gene (Matsunaga et al, 1999;Shin et al, 2006;Ni'mah et al, 2016;Hertanto et al, 2017). Irine et al (2013) also used cytochrome b gene to identify species of tiger, cat, and dog. In addition to cytochrome b gene, another unique region contained in animal mitochondrial genome is 12S rRNA gene.…”
Section: Introductionmentioning
confidence: 99%
“…Previously developed feline-specific PCR assays were based on mitochondrial whole genome: 672 bp (Abdulmawjood et al 2003); 672 bp (Abdel- Rahman et al 2009); ND4 gene (274 bp) (Ilhak & Arslan 2007); 12S rRNA (108 bp) (Martin et al 2007); cytb gene (180 bp) (Tobe & Linacre 2008); and cytb gene (331 bp) (Irine et al 2013). These assays involved considerably longer amplicons which are assumed to be fragmented under commercial food processing treatments, causing PCR failure or truncated PCR products.…”
Section: Results and Discussion Feline Species Specificitymentioning
confidence: 99%
“…To study the comparative stability of the newly designed 69 bp amplicon and one of the previously documented 108 bp targets (the shortest of the previously documented targets 672 (Abdel- Rahman et al 2009), 331 (Irine et al 2013), 274 (Ilhak & Arslan 2007), 180 (Tobe & Linacre 2008) and 108 bp (Martin et al 2007)). PCR was performed with a 50 ng feline DNA template after autoclaving feline meats at 135°C for 30, 60, 90, 120 and 150 min under 0.3 MPa and microwave cooking at 600 and 700 W for 30 min.…”
Section: Comparison Of Target Dna Stabilitymentioning
confidence: 99%
“…Previously, cat meat was detected by PCR assay targeting a 672-bp (Abdulmawjood et al 2003;Abdel Rahman et al 2009); 274-bp (ND4) (İlhak and Arslan 2007); 108-bp (12S ribosomal RNA (rRNA)) (Martín et al 2007); 180-bp (Tobe and Linacre 2008), and 331-bp sites of cytb gene (Irine et al 2013). However, it has been assumed that longer amplicons are thermodynamically less stable than the shorter ones under environmental decomposition or degradation by food processing treatment Ali et al 2011;Rahman et al 2014).…”
Section: Specificity Testmentioning
confidence: 99%